2018
DOI: 10.3889/oamjms.2018.367
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Functioning and Psychosocial Problems in Children with Beta Thalassemia Major

Abstract: BACKGROUND:Beta thalassemia major is considered one of the serious health problems and the commonest hemoglobinopathy in Egypt that creates a burden not only on health system but also on the affected families and children who become vulnerable to emotional, social, psychological and behavioural problems.AIM:This study was designed to assess the psychosocial burden and the adaptive functioning in children with beta-thalassemia major.SUBJECTS AND METHODS:A group of 50 children with thalassemia major and 50 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
4
17
0
Order By: Relevance
“…This confirms findings of a previous study done among 60 Iranian children with thalassaemia major who reported higher rates of behavioural problems in emotional, conduct, hyperactivity, peer relationship, social and all states compared to healthy children [21]. Similar findings were reported in few other small-scale studies [22,23]. However, ours is the largest of such studies.…”
Section: Discussionsupporting
confidence: 92%
“…This confirms findings of a previous study done among 60 Iranian children with thalassaemia major who reported higher rates of behavioural problems in emotional, conduct, hyperactivity, peer relationship, social and all states compared to healthy children [21]. Similar findings were reported in few other small-scale studies [22,23]. However, ours is the largest of such studies.…”
Section: Discussionsupporting
confidence: 92%
“…From a list of public primary schools in this district, a representative number of public schools (4 schools) were randomly chosen. In each school, children who had any chronic disease or any disability known to affect cognitive performance or impacting behavior were excluded [14,15] (e.g., children with hearing or visual defects, children with history of neonatal traumatic brain injury or meningitis, children with endocrinal diseases or hormonal disturbances, or children with mental affection or motor disability). Then, a systematic random sampling of students from grade 3 to grade 5 was performed.…”
Section: Settingmentioning
confidence: 99%
“…One of the chronic and genetic blood diseases is thalassaemia (Elzaree et al., 2018 ). In this disease which is more prevalent in the Mediterranean countries (Behnam Vashani et al., 2015 ), the patient needs repeated blood transfusion and use of iron chelating drugs to survive (Ishfaq et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, there are about 25000 people with this disease (Razzazan et al, 2014 ). These patients have several physical problems including severe chronic anaemia, hepatosplenomegaly, bone changes especially in face and head (Zarea et al., 2012 ), facial pigmentation, growth failure (Elzaree et al., 2018 ) and pubertal delay or failure (Ozturk et al., 2017 ). In addition to the physical problems, patients also suffer from the psychosocial problems such as depression, anxiety, anger, limitation in the social communication (Ozturk et al., 2017 ), social isolation, aggression, decrease in self‐esteem and being different (Ishfaq et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%